2014
DOI: 10.3920/qas2013.0371
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally enhanced wheat-oat bread with reduced acrylamide level

Abstract: Consumption of nutritionally enhanced wheat-oat bread naturally rich in β-glucans originating from extra-wholemeal oat flour with improved digestibility by lactic fermentation provides unambiguous health benefits associated with a slower blood glucose release and a higher subjective satiety determined by a postprandial study. However, an undesirable elevated acrylamide formation in the crust of bread was observed due to a high level of a main precursor amino acid L-asparagine in oat flour. Lactic fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…In the present study, the highest acrylamide levels in biscuits were determined in the oat biscuits. It was reported that free asparagine content of the oat flour is high and result of the present study is in consistent with that finding [62]. Cocoa beans contain free asparagine and roasting process increases acrylamide in cocoa [63].…”
Section: Resultssupporting
confidence: 82%
“…In the present study, the highest acrylamide levels in biscuits were determined in the oat biscuits. It was reported that free asparagine content of the oat flour is high and result of the present study is in consistent with that finding [62]. Cocoa beans contain free asparagine and roasting process increases acrylamide in cocoa [63].…”
Section: Resultssupporting
confidence: 82%
“…l-Asparaginase effect on the acrylamide formation in cereal-based products was investigated in wheat cracker products [43], corn-based foods [52], short-dough biscuits [53,54], fried-dough pastry [51], gingerbread [42], and in bread [55][56][57]. All these authors reported a significant reduction in acrylamide levels upon l-asparaginase addition, although the specific conditions for the use of this enzyme should be finely tuned to make its use reliable in terms of costs at the industrial level.…”
Section: Cereal-based Matrices For L-asparaginase Treatmentmentioning
confidence: 99%
“…Capuano et al [56] used a bread crisp model system made of flour, water, and yeast. This resulted in a 46% decrease of acrylamide in the bread crust [57]. l-Asparaginase was added to 2000 U/kg of flour.…”
Section: Cereal-based Matrices For L-asparaginase Treatmentmentioning
confidence: 99%
“…Lactic acid fermentation used for dough preparation of crispbread produced a 75% decrease in acrylamide content, an effect that was attributed to a drop in the pH from 6.0 in the control to 3.7 (Claus et al ., ). Also, lactic acid fermentation of oat flour by Lactobacillus plantarum and 30% substitution of extra‐wholemeal oat flour with fermented oat sourdough led to more attractive organoleptic quality of wheat–oat‐fermented bread and to a decrease of pH value which suppressed acrylamide level up to 10% (Ciesarova et al ., ).…”
Section: Resultsmentioning
confidence: 97%